PENGEMBANGAN MODUL AJAR MATERI TEKS EKSPLANASI BERBANTUAN AI DI SMA NEGERI 1 BATANG KUIS - Gabriella Secilia Silitonga; Oni Catrine Joana Simbolon; Uci Amelia; Dimas Bayu Kumbara; Febby Meilia; Najla Mutia Nasution; Trisnawati Hutagalung; Nurul Azizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an AI-assisted explanatory text teaching module for twelfth-grade students at SMA Negeri 1 Batang Kuis. The research employs the ADDIE development model with a descriptive qualitative approach. The research subjects consist of an Indonesian language teacher and 30 twelfth-grade students. Data were collected through interviews, documentation of the school’s teaching materials, material expert validation questionnaires, and learning outcome tests planned to measure the module’s effectiveness. The results indicate that the teaching materials currently used at the school are limited to textbooks and simple modules that do not yet provide reading-aloud exercises, audio models, or concept maps. The developed teaching module obtained a validation score of 87.5% from the material expert validator, categorized as highly feasible, thus making it suitable for use as a supplementary teaching material for explanatory text learning. The module’s effectiveness was planned to be measured through improvements in explanatory text writing scores and achievement of the minimum competency criteria (KKM); however, effectiveness testing was not carried out in this study because it focused on the product development stage.